Influence of Trichoderma as a seed treatment on the growth and yield of groundnut under saline environment - Abdullah Taufiq; Eriyanto Yusnawan (Journal of Degraded and Mining Lands Management, 2020)
Agriculture lands in coastal areas face the risk of increasing salinity due to the influence of sea water. Salinity poses complex problems for plants at all growth stages which are difficult to be addressed. Trichoderma is a microorganism known to promote plant growth and to induce plant tolerance to abiotic stresses including salinity. The research aimed to evaluate effective Trichoderma for improving groundnut growth and yield in a saline environment. The research was conducted on saline soil (EC >8 dS/m) at Gesikharjo Village, Palang Sub District, Tuban District from July to October 2019. Treatments were combinations between N and P fertilization, and four Trichoderma strains and these treatments were arranged in a randomized completely block design with six replicates, using Hypoma 1 groundnut cultivar.  Soil fertility and salinity, growth, yield and yield components were recorded as observed parameters. The results showed that NP fertilization on high salinity soils (ECs of 8.80-15.91 dS/m) with low N and high P had no significant effect on all variables compared to those of N fertilization. Applications of Trichoderma increased plant height and minimized plant death as indicated by a higher percentage of plant population at harvest compared to that of without inoculation. Among the four Trichoderma strains, Trichoderma #3 and Trichoderma #4 showed more effective than the other two strains in improving plant growth based on the shoot dry weight at the R1 phase, plant height and percentage of plant population at harvest. The positive effect of Trichoderma #3 and #4 could be due to the ability to promote plant growth as well as to induce plant resistance against salinity stress. The results suggested that Trichoderma was effective to alleviate salinity stress on groundnut crops. This research was the first trial carried out in the field and therefore needs to be further investigated, including Trichoderma formulations and application techniques.